A controlled study to assess the effects of vaccination against Newcastle disease in village chickens - Barman, LR; Flensburg, MF; Permin, A; Madsen, M; Islam, MR (Bangladesh Veterinarian, 2011)
The effect of vaccination against Newcastle disease (ND) in free range village chickens was assessed in a controlled field study. Based on the results of a baseline survey, 12 vaccinated and 12 unvaccinated backyard chicken flocks from two adjacent villages were selected and followed for six months. Serum antibody levels were measured on four occasions. All mortalities were recorded and the cause of death was established by necropsy. Selected ND-suspected cases were subjected to virus isolation, and pathogenicity of two selected isolates was measured in terms of mean death time (MDT) of inoculated chicken embryos. The baseline survey revealed that approximately 90% of the village families reared chickens of which only 11% regularly vaccinated their chickens against ND. Another 14% occasionally vaccinated their chickens and 75% did not vaccinate at all. In the flocks under study, antibody titres increased in vaccinated and unvaccinated chickens. About 75% of unvaccinated and 96% of vaccinated mature chickens (>28 weeks of age) had antibodies to ND virus (NDV), but the level was significantly higher in vaccinated birds. A striking difference in seroconversion was observed in unvaccinated and vaccinated younger birds: 3.3% vs. 55.1% in chicks (<9weeks of age) and 7.3% vs. 80.3% in growing pullets (9-28 weeks of age), respectively. Mortality due to ND was significantly higher in unvaccinated flocks (21.6%) than in vaccinated flocks (4.9%). Most of these mortalities occurred in growing pullets and chicks. Eight selected samples were positive for NDV when subjected to embryo inoculation and haemagglutination inhibition (HI) test. Two of the isolates were further characterized: both were velogenic pathotype with MDT of <60 hours. It is suggested that vaccination against ND could significantly reduce mortality in village chickens. DOI: 10.3329/bvet.v27i2.7555 Bangl. vet. 2010. Vol. 27, No. 2, 56-61